RxSports Carnival 2023: a triumph of sportsmanship and unity / Nur Natasha Mohd Roslan and Aida Azlina Ali - Mohd Roslan, Nur Natasha; Ali, Aida Azlina (Faculty of Pharmacy, 2024)
The RxSports Carnival organized by the Society of Pharmacy Students (SOPHYS) in partnership with Sekretariat Mahasiswa Fakulti Farmasi (SMF) was a successful three-day event held from December 8 to December 10, 2023. The program aimed to encourage an active lifestyle and foster positive relationships among students, alumni, and faculty staff. The diverse range of sports contested during the carnival included ultras, futsal, badminton, netball, volleyball, frisbee, aerodance, tug-of-war, as well as E-sports like Valorant, Mobile Legends, and PUBG. On the first day, PUBG, Valorant, and ultras were contested, showcasing sportsmanship, with final-year students claiming victories in both E-sports. The second day saw even more challenging competitions with badminton, futsal, volleyball, and Mobile Legends taking place from 8 a.m. until 12 p.m. Notably, the finals for futsal and female volleyball were dominated by final-year students, while alumni teams dominated the male categories. In badminton, final-year students secured championships in all categories, including men’s double, women’s double, and mixed double. The Mobile Legends competition was won by San Pedro College Davao, Philippines.